Pengaruh Penambahan Kadar Plastik Jenis Polypropylene Terhadap Titik Lembek Aspal Modifikasi - Afrianti, Dwi; Reza, Muhammad; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The country of Indonesia is ranked second in the world for producing plastic waste, so the use of plastic waste must be carried out. The use of plastic waste as an additive in asphalt mixtures can improve the quality of asphalt concrete pavement and also reduce plastic waste. This study aims to determine the effect of adding plastic waste to the characteristics of modified asphalt layer AC-BC (Asphalt Concrete-Binder Course). The research was carried out in an experimental laboratory with the type of plastic used PP the percentage addition of plastic content was 0%, 2%, 3%, 4%, 5%, and 6% by weight of asphalt. The results showed that the addition of plastic had increase the softening point of asphalt and decrease the penetration value of asphalt.Keywords: modified asphalt, marshall characteristics, laston AC-BC, plastic